Islamic Philanthropy and the Third Sector: The Portrait of Zakat Organizations in Indonesia - Dani Muhtada (Islamika Indonesiana, 2014)
This paper discusses the role of zakat organizations as the emerging Third Sector in Indonesia. It presents the profiles of three currently leading zakat organizations: Rumah Zakat Indonesia (RZI), Dompet Dhuafa (DD), and Pos Keadilan Peduli Ummat (PKPU). This paper highlights that the zakat organizations play an important role in serving public needs in Indonesia. They offer many services in such areas as health, economy, education, agriculture, and disaster reliefs. Competition does exist among zakat organizations, particularly if they operate in the same areas and target the same segment of donors (e.g., wealthy Muslims in urban areas). This paper argues that some more efforts are still needed to strengthen the roles of zakat organizations as part of the Indonesian third sector. This could be achieved through strengthening the accountability and the transparency of zakat management as well as by encouraging zakat organizations to allocate more funds for economic development programs. Allocating more funds for economic development programs would make zakat organizations more powerful in promoting social welfare in the society.